OS REGIMES DO GOSTO NAS PRÁTICAS DA FEIRA LIVRE: UM ESPETÁCULO DE VER, SENTIR E CONSUMIR - ELAINE CRISTINA DE QUEIROZ SILVA (2022)
The general objective of this research is to observe the production of meanings in street fairs and how they formed from their genealogy, referencing a semiotics of experiences, based on discursive semiotics and its recent developments, such as semi-symbolism and socio-semiotics. Our methodology limited to bibliographic and descriptive research, punctuating the narrative statements inscribed in historical records and in contemporary practices. As specific objectives, we set out to organize how the regimes of meaning and interaction built in the practices of street fairs over time and the changes in meanings caused by the COVID-19 pandemic. As it is a social object, we use different corpora for the analyzes in an exploratory character that we list in three categories: 1) bibliographic survey based on historical records that denote the meanings of fairs as a social and cultural practice through axiological processes; the linguistic and extralinguistic factors, such as expressions and proverbs instituted in the fairs of the Middle Ages; and the changes in practices caused by the epidemics that changed the context of trade in this period; 2) an on-site study at the street fair of Guanandi, in the capital Campo Grande, for a socio-semiotic analysis of social practices using images of the day of the fair captured through recordings made using a cell phone; 3) audiovisual text, using television journalistic report produced in the fair environment, which we dissected in two clippings to demonstrate the changes of meanings in fair practices in times of the COVID-19 pandemic, observing the generative path of meaning in the content plan of journalistic material and the semi-symbolic relationships in a frozen image (freeze frame) or framing. The theoretical framework focuses on the ideas of scholars, such as: Greimas (1973), Landowski (2004), Floch (1985), Pietroforte (2019), Barros (2001), Fiorin (2018), Oliveira (2014) and Bueno (2014), among other bibliographic contributions aimed at deepening the investigations, among these: Bourquelot (1865), Huvelin (1897), Goffman (1986), Le Goff (1990), Bateson (2000), Sato (2012) ), Bernardo (2014) among others. This work developed on the postulates of language studies, in addition to providing new perspectives for the elaboration of new research in Semiotics, made it possible to understand that the semiotic syncretism of the street fair jumps from figuration, tastes and relationships of an affective consumption based on processes axiological. Keywords: Street fair; Discursive semiotics; Semi-symbolism; Sociosemiotic.